Antioxidant and antibacterial properties of bacterial cellulose— Indonesian plant extract composites for mask sheet - Anastasia Wheni Indrianingsih, Vita Taufika Rosyida, Wuri Apriyana, Septi Nur Hayati, Cici Darsih, Khoirun Nisa, Dwi Ratih (Journal of Applied Pharmaceutical Science, 2020)
Cellulose constructed by microbial culture is called as bacterial cellulose (BC). BC has a high purity with no lignin, pectin, and hemicellulose commonly found in plant cellulose and also has a high degree of crystallinity so that the microfiber contained in it is tightly bound together and forms robust and elastic webbing. This study aims to provide a face mask sheet, wherein the sheets are made from BC, which is obtained from the fermentation of coconut water using Acetobacter xylinum. The plant extracts used were green tea leaf extract (Camellia sinensis), roselle flower petals (Hibiscus sabdariffa), and Hibiscus rosa-sinensis L. flower extract (a red and pink variant of color). The antioxidant assay using the DPPH test for the BC with plant extracts was evaluated. The result showed that the highest antioxidant activity was owned by BC green tea extract (IC50 80.9 ppm), followed by BC red hibiscus extract (IC50 438.8 ppm), BC roselle extract (IC50 505.1 ppm), and BC pink hibiscus extract (IC50 1015 ppm). Antibacterial testing was carried out using Salmonella typhimurium, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The growth of bacteria incubated in BC extract with 37oC for 24 hours was carried out by optical density reading (OD) at 600 nm with ELISA microplate reader. The results obtained showed that, with extract concentrations between 125 and 500 ppm, BC roselle extract had the highest inhibitory activity against P. aeruginosa and E. coli. The BC plant extracts were also characterized using SEM, FTIR, and X-ray diffraction technique for their morphological structure, functional groups, and crystallinity. This result showed that BC with the addition of plant extracts is a promising candidate for mask sheet application with natural antioxidant and antibacterial activity.
Keywords: Bacterial cellulose, antioxidant, antibacterial, plants extract, face mask sheet.